Gender (in)equality in (European) society - Slijepcevic, Dusanka; Vilic, Dragana (Technium Social Sciences Journal, 2023)
The subject is gender inequality in Europe from 2020 to 2030. What are the measures to problem solving or the Gender Equality Strategy (2020 – 2025) challenges? The scientific goals are scientific description, understanding and causal explanation of problem, based on secondary data by international organizations, EU statistical institutions and measures of the Strategy, from the scientific theory of liberal feminism. The methodology refers to the analysis of problem indicators and the synthesis of proposals for its solutions. The results relate to the expanding the scientific knowledge of European society and its problems, and a pragmatic explanation with an overview of solutions.